Determinasi Pelayanan : Kepatuhan Pajak Perspektif Sosiologi Hukum - Sanusi Sanusi; Dedi Roy; Dewi Yanti (Penerbit Goodwood, 2025)
Purpose: This study aims to examine knowledge and understanding of the implementation of the tax system, including the quality of tax services provided by authorities, and to evaluate various factors influencing taxpayer compliance in Indonesia. Methodology: A juridical and sociological legal approach is used in this study, applying descriptive-analytical methods. Data were collected from literature and relevant sources, then analyzed qualitatively by organizing information into coherent narratives to draw conclusions. Results: Low tax compliance is influenced by several factors: limited public knowledge of tax regulations, low financial literacy, insufficient public awareness campaigns, and underutilized benefits of modernized tax services. Taxpayers are often unaware of the incentives offered through compliance. Additionally, cultural variables such as the perception of tax obligations as communal ideals—shaped by justice and social responsibility—play a role. However, there is still resistance due to unfamiliarity with online administrative procedures. Conclusion: Voluntary tax compliance improves when tax policies are perceived as fair and the benefits of paying taxes are recognized. Ethical and environmental elements, particularly those embedded in Indonesia’s communal culture, significantly influence taxpayer behavior. Although legal enforcement can increase compliance, social norms have limited impact on actual tax practices. Ultimately, tax compliance directly supports national development and public welfare. Limitations: This qualitative study may reflect some degree of subjectivity, and its findings are not universally generalizable. Citations are included to minimize bias. Contribution: The study suggests simplifying tax return terminology, utilizing free tools for profiling and monitoring taxpayer behavior, and improving outreach through Business Development Services (BDS) to enhance public understanding and compliance.